(untitled) (Proceedings International Conference on Fisheries and Aquaculture, 2024)
The introduction of the Sound Navigation and Ranging (SONAR) technology in recent years to help fishers detect changes in bathymetry, or help locate aggregations such as fish schools, underwater formations among others using sound waves transmitted from on-board the vessel has received little attention from the scientific community. With this equipment, crew on board vessels easily identify fish schools, aggregations and bathymetry anomalies for successful purse-seine operations. The study was conducted to determine how purse-seine fishers have adopted SONAR and the factors influencing their adoption decisions. Little empirical data exists on adoption of this technology in Ghana. Utilising the extended technology acceptance model (TAM3), and a validated structured questionnaire, 161 fishers were surveyed from three fishing communities in the Central region of Ghana. With the help of SmartPLS 4.0, partial least squares structural equation modelling (PLS-SEM) was used for data analysis. The results showed that, perceived ease of use, perceived usefulness, and subjective norms accounted for 38% of the variance in the behavioural intention of purse-seine fishers to adopt SONAR whiles behavioural intention predicted 8% of the variation in their use behaviour of the technology. The results indicate that, as the fishers perceive SONAR to be useful and easy to use, and important people like vessel owners, family and friends thinking that the fishers should use the technology, these significantly influence their behavioural intention to adopt SONAR and ultimately their adoption behaviour. We recommend that the Fisheries Commission of Ghana should leverage on the characteristics of SONAR as ease of use and usefulness as well as the influence of vessel owners, family and friends to drive its adoption in the study area.